"Billy": split bill mobile application - Susanto, Wesley (Nanyang Technological University, 2024)
This project focuses on the development of a mobile application that handles bill splitting among users. Split bill application helped in addressing the challenge of managing group expenses, especially during meals, outings, travels, and household expenses. This application will allow user to customize their profile, and also allow user to track on how much they owed and how much they owe, with further details on which transaction were the unsettled payments are.